The Cartonnage of Paysetjenfy (SMDAN 1353) Found in Dra Abu el-Naga - Llanos, Lucía Díaz-Iglesias (Zeitschrift für ägyptische Sprache und Altertumskunde, 2024)
In 2016, the Spanish Mission at Dra Abu el-Naga (hereafter SMDAN), directed by José M. Galán, found eight cartonnage mummy-cases. They were torn into pieces and discovered in the largest shaft and burial chamber of a group of funerary and commemorative structures that are located to the south-west of the open courtyard of the tomb-chapel belonging to Djehuty (TT 11). Built during the late 17 th or early 18 th dynasties, the shaft and chamber were thoroughly plundered and repeatedly reused over several centuries, especially during the Third Intermediate Period. One of the cartonnages, SMDAN 1353, made for Paysetjenfy, has been selected for a comprehensive analysis of its decoration, including its state of preservation, technique of execution and its textual and iconographic content. A combined study of the archaeological context and the materiality of this artefact, with a search for parallels for its decoration and an investigation into the genealogical and prosopographic information concerning its owner are undertaken. This type of research will help to contextualise this cartonnage within the Theban manufacturing industry of cartonnage cases and the complex social structure of families bearing the highest ranks in the priesthood of Amun during the 22 nd dynasty.